Respostas

2014-07-09T06:52:52-03:00
A) - 9x + 23 = -58 + 729
   - 9x + 23 + 58 - 729 .(-1)
     9x - 23 - 58 + 729
     9x - 81 + 729 
     9x + 648 = 0
     9x = - 648 
     x = - 648 / 9
     x = - 72

b) - 2x + 2 + 3x = 4 + 3x + 14
    - 2x + 2 + 3x - 4 - 3x - 14 = 0 .(- 1)
      2x - 2 - 3x + 4 + 3x + 14 = 0
      2x + 16 = 0
      2x = - 16
      x = - 16 / 2
      x = - 8

c) 3x - 2 + 5 - x = 0
    2x + 3 = 0 
    2x = - 3
    x = - 3 / 2

d) 2 / 3 + x / 2 - 5 = x / 3 + 1
    4 + 3x - 30 / 6 = 2x + 6 / 6
    4 + 3x  - 30 - 2x - 6 = 0
    x - 32 = 0
    x = 32

e) 6 (x + 4) / 7 - 1 / 2 = x 
    6x + 24 / 7 - 1 / 2 = x 
    2 (6x + 24) - 7 / 14 = 14x / 14
    12x + 48 - 7 - 14x = 0
    - 2x + 41 = 0 . ( - 1 )
    2x - 41 = 0
    2x = 41
    x = 41 / 2

f) y + 9 / 5 - 4 - 2y / 10 = y / 2
   2 (y + 9) - (4 - 2y) / 10 = 5y / 10
   2y + 18 - 4 - 2y - 5y = 0
   - 5y + 14 = 0 . ( - 1)
   5y - 14 = 0
   5y = 14
   y = 14 / 5